Contemporary insights into neuroimmune interactions across development and aging - Yeo, Xin Yi; Choi, Yunseon; Hong, Yeonhee; Kwon, Hyuk Nam; Jung, Sangyong (Frontiers in Neurology, 2025)
Initially considered distinct systems with independent physiological functions, recent evidence highlights the crucial role of active crosstalk between the nervous and immune systems in regulating critical physiological and neurological processes and immunological homeostasis. The identification of a direct body-brain circuitry allowing the monitoring of peripheral inflammatory responses, a unique skull bone marrow source of immune cells to the central nervous system (CNS), and the physical interface of the blood-brain barrier with the meningeal system suggest direct intersystem interactions, which can be further modulated by the local tissue environment, allowing non-neurological factors to influence neurological outcomes and vice versa. While there is a recognized age-dependent decline in both neurological and immune system function, in part due to the natural accumulation of cellular defects and the development of chronic systemic inflammation, it is unclear if the pre-existing bidirectional feedback mechanisms between the neurological and peripheral immune system plays a role in shaping the system decline, beyond commonly investigated pathological conditions. In this review, we will explore the effect of aging on the bidirectional communication between the neurological and immunological systems and attempt to understand how the inevitable age-dependent alterations of the interaction may concurrently drive immunosenescence, normal neurological decline, and neuropathological progression.